The war in Croatia and Bosnia-Herzegovina, 1991-1995 - Magaš, Branka; Žanić, Ivo, 1954-; Malcolm, Noel, 1956- (London : Frank Cass, 2001)
This work provides an understanding of the wars in Croatia and Bosnia-Herzegovina. These two interdependent wars were the greatest armed conflicts in Europe in the second half of the 20th century. This work provides an analysis of their successes and failures.
Foreword / Noel Malcolm -- The road to war / Stjepan Mesić -- The first phase, 1990-1992 : the JNA prepares for aggression and Croatia for defence / Martin Špegelj -- The war in Slovenia and Croatia up to the Sarajevo ceasefire / Anton Tus -- Operations Flash and Storm / Ozren Žunec -- Termination and aftermath of the war in Croatia / Dugan Bilandžić -- The road to war / Rusmir Mahmutćehajić -- The first phase, 1992-1993 : struggle for survival and genesis of the army of Bosnia-Herzegovina / Jovan Divjak -- Civilian-military relations in Bosnia-Herzegovina 1992-1995 / Marko Attila Hoare -- Serb war effort and termination of the war / Norman Cigar -- The international community's response to the crisis in Former Yugoslavia / Paul Williams -- International military responses to the Balkan wars : crises in analysis / Warren H. Switzer -- Addendum: Who wants to be a soldier? : the call-up crisis, an analytical overview of media reports / Ofelija Backović, Miloš Vasić and Aleksandar Vasović -- Appendix: Chronology 1985-1995
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: chorvatská válka za nezávislost (1991-1995); válka v Bosně a Hercegovině (1992-1995); Croatian War of Independence (1991-1995); Bosnia and Herzegovina, civil war (1992-1995); kolektivní monografie; e-knihy online; collective monographs; e-books online